2003
DOI: 10.1103/physrevb.68.195420
|View full text |Cite
|
Sign up to set email alerts
|

Towards chemical identification in atomic-resolution noncontact AFM imaging with silicon tips

Abstract: In this study we use ab initio calculations and a pure silicon tip to study the tip-surface interaction with four characteristic insulating surfaces: ͑i͒ the narrow gap TiO 2 ͑110͒ surface, ͑ii͒ the classic oxide MgO ͑001͒ surface, ͑iii͒ the ionic solid CaCO 3 (101 4) surface with molecular anion, and ͑iv͒ the wide gap CaF 2 ͑111͒ surface. Generally we find that the tip-surface interaction strongly depends on the surface electronic structure due to the dominance of covalent bond formation with the silicon tip.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
(46 reference statements)
2
39
1
Order By: Relevance
“…But, at the same time, it opens the possibility, through a combination of experiments and theoretical modeling, to characterize the tip and to make a direct identification of defects and adsorbates on technologically relevant oxide surfaces. Calculations with model tips, like an MgO cube, 13 provide a basic understanding of the contrast in the protrusion and hole modes in TiO 2 in terms of electrostatic interactions controlled just by the tip apex polarity, as also proposed for other ionic surfaces. 14 The neutral case has been explained as due to the onset of covalent bonding with a nonpolar model Si tip.…”
Section: Introductionmentioning
confidence: 99%
“…But, at the same time, it opens the possibility, through a combination of experiments and theoretical modeling, to characterize the tip and to make a direct identification of defects and adsorbates on technologically relevant oxide surfaces. Calculations with model tips, like an MgO cube, 13 provide a basic understanding of the contrast in the protrusion and hole modes in TiO 2 in terms of electrostatic interactions controlled just by the tip apex polarity, as also proposed for other ionic surfaces. 14 The neutral case has been explained as due to the onset of covalent bonding with a nonpolar model Si tip.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed decay length of the interaction force in this model is about one order of magnitude perÅ and thus sufficiently small to explain atomic scale contrast on ionic surfaces. In a series of papers using different model tips on ionic as well as oxide surfaces, Shluger et al point out the importance of the polarization of both, tip and sample surface [14][15][16][17][18] . These extensive calculations consider, in particular, polarization effects; however, it seems difficult to separate them from the different other interactions also described in these works.…”
Section: Introductionmentioning
confidence: 99%
“…Our purpose is to show how SRE contribution can reproduce trends and orders of magnitude reported in the experiments by Gross et al 56 . However, it is not our intention to fit their results since that would require a fully atomistic description involving a complex simulation process [14][15][16][17][18] . …”
Section: Introductionmentioning
confidence: 99%
“…2(b)]. The electron transfer between tip and surface is calculated by summing all the Mulliken charges in the tip and surface at the relevant tipsurface separation and comparing this with a reference calculation with the tip at 2 nm from the surface [9]. This is equivalent, by definition [assuming infinite accuracy in the partial density of states (PDOS) and after normalization] to integrating over all the tip and surface states of the PDOS.…”
mentioning
confidence: 99%
“…We considered both spin-polarized and non-spin-polarized methods, and we found that it does not make a qualitative difference to the results. The size of the slabs used to represent the surfaces in calculations was determined by checking that the area was large enough to avoid spurious tip-tip interactions and deep enough so that the physical and electronic structure was well converged [9]. The gap between the top of the tip and the bottom of the slab was always at least 2 nm to avoid spurious tip-slab interactions.…”
mentioning
confidence: 99%